2022
DOI: 10.1007/s40261-022-01201-2
|View full text |Cite
|
Sign up to set email alerts
|

FRAGILE-COLCOVID19: A Clinical Trial Based on Early Administration of an Oral Combination of Colchicine and Prednisone in Elderly Patients with COVID-19 in Geriatric Facilities

Abstract: Background Unprotected and fragile elderly people in nursing homes experienced the highest mortality rates during the initial coronavirus disease 2019 (COVID-19) pandemic. Objective Our aim was to study the role of two oral anti-inflammatory drugs, colchicine and prednisone, in elderly patients with COVID-19 in geriatric centers. Methods A phase II/III, randomized, controlled, multicenter clinical trial was performed in a geriatric population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Colchicine administration in moderate to severe COVID-19 patients showed less mortality and a higher discharge rate in comparison to the control [143]. A pilot RCT based on 40 adults with obesity and metabolic syndrome reported that a dosage of 0.6 mg colchicine twice daily for 3 months reduced pro-inflammatory molecules including CRP, IL-6, resistin, along with vascular-related proteins (such as oxidized low-density lipoprotein receptor, phosphodiesterase 5A) [144]. Another clinical trial assessed combination oral therapy of prednisone (60 mg per day for 3 days) and colchicine (1-1.5 mg per day for 3 days and then 0.5 mg per day for 11 days) on 25 patients and 29 patients were chosen as control.…”
Section: Colchicinementioning
confidence: 99%
“…Colchicine administration in moderate to severe COVID-19 patients showed less mortality and a higher discharge rate in comparison to the control [143]. A pilot RCT based on 40 adults with obesity and metabolic syndrome reported that a dosage of 0.6 mg colchicine twice daily for 3 months reduced pro-inflammatory molecules including CRP, IL-6, resistin, along with vascular-related proteins (such as oxidized low-density lipoprotein receptor, phosphodiesterase 5A) [144]. Another clinical trial assessed combination oral therapy of prednisone (60 mg per day for 3 days) and colchicine (1-1.5 mg per day for 3 days and then 0.5 mg per day for 11 days) on 25 patients and 29 patients were chosen as control.…”
Section: Colchicinementioning
confidence: 99%